The Effectiveness of Duolingo Application in Vocabulary Mastery for English for Young Learners in MIN 1 Malang - Novitasari, Elma Diana; Putera, Alam Aji (English Edu: Journal of English Teaching and Learning, 2024)
English has been used as the mother tongue in several countries. Learning English for young learners is especially necessary because we will understand the meaning of English sentences by learning vocabulary. English is also a complex language to learn, therefore the teacher must think of something that can change students' views on learning English. In learning EYL, the teacher must consider engaging learning that keeps students from getting bored, such as learning English vocabulary using media. One example of an application or technology-based learning media is the Duolingo application. Duolingo is a learning medium in the form of a practical application for learning vocabulary. It is an application that can attract students' interest in learning. This study aims at determining how suitable the Duolingo application is for young English learners. This study used Quasi Experimental quantitative research with 22 students in class 5G as the experimental class and 22 students in class 5H as the control class subjects. Researcher choose this Quasi-Experimental because she want to know the difference before and after. Students were given treatment three times using the Duolingo application and provided a pre-test before treatment and a post-test after treatment. The results showed significant differences between the pre-test and post-test of each class. The test results were tested by T-Test: Two-sample assuming equal variances, done with Microsoft Excel. The results of the statistical test showed that the t-value was 0.394, which could be concluded to be less than the t-table, which was 2.080. These results indicate that the Duolingo application is practical for students' vocabulary mastery.